Blocking TXNIP reduced IL-1β Induced chondrocyte cell inflammation: Blocking TXNIP reduces IL-1β-induced chondrocyte inflammation - Xu, Shenggui; Lin, Weimin; Lin, Wang; Lin, Chengshou; Guo, Weizhong (Cellular and Molecular Biology, 2023)
Osteoarthritis (OA) is the most common joint disease in the elderly and is characterized by progressive and irreversible degeneration of articular cartilage, particularly cartilage loss and callus formation. This study would like to investigate the important role and the molecular mechanism of OA progression following interleukin 1β (IL-1β)-induced chondrocyte injury regulated by TXNIP. In this study, high-purity mouse chondrocytes were obtained by enzymatic two-step digestion for primary culture. Toluidine blue staining and type II collagen immunofluorescence were used to identify cells through histochemical staining after slide mounting. The relative expression of TXNIP was detected by immunohistochemical staining and qRT-PCR.Aiming at the shRNA sequence of the TXNIP gene, the shRNA expression vector was constructed and packaged with lentivirus to form the lentiviral vector shTXNIP. After inhibiting the expression of TXNIP by transfecting shTXNIP into normal mouse chondrocytes, the CCK-8 kit was used for detecting its effect on cell proliferation after transfection, and the effect on chondrocyte apoptosis was detected by flow cytometry. The staining kit was used to detect the effect of TXNIP knockout on chondrocyte aging, and the differential expression of TNF, IL-6, MMP3, MMP13, ADAMTS-5 and type II collagen genes in chondrocytes was detected by RT-PCR and Western-bolt. Western blot was used to detect the expression of upstream-related protein P-ERK, downstream-related protein NLRP3 and Caspase1 after inflammatory injury of mouse articular chondrocytes. Results showed that the expression level of TXNIP in chondrocytes induced by different concentrations of il-1β was proportional to the concentration. After silencing TXNIP by shRNA, cell proliferation increased, chondrocyte apoptosis was weakened, and chondrocyte aging was weakened. The differential expression of genes such as TNF, IL-6, MMP3, MMP13, ADAMTS-5 and type II collagen and the differential expression of protein levels were relatively decreased. In addition, the expression of the upstream-related protein P-ERK did not change much when TXNIP was silenced, and the expression levels of the downstream-related proteins NLRP3 and Caspase1 were slightly reduced. In conclusion, silencing TXNIP can inhibit il-1β-induced chondrocyte apoptosis and aging, and has a positive effect on cell proliferation. However, this study has not clarified the molecular mechanism involved in TXNIP and the process of its signaling expression pathway.